2016
DOI: 10.1038/nm.4050
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity and depression: new insights from stress and rapid-acting antidepressants

Abstract: Depression is a common, devastating illness. Current pharmacotherapies help many patients, but there are high rates of partial- or non-response and the delayed onset of the effects of antidepressant leave many patients inadequately treated. However, new insights into the neurobiology of stress and human mood disorders have shed light on mechanisms underlying the vulnerability of individuals to depression and have pointed to novel antidepressants. Environmental events and other risk factors contribute to depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
960
5
25

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,264 publications
(1,024 citation statements)
references
References 197 publications
(201 reference statements)
34
960
5
25
Order By: Relevance
“…2). However, Zanos et al found that both ketamine and (2R,6R)-HNK have no significant effect on mTOR phosphorylation and BDNF levels at 1 h after treatment, which is not consistent with previous studies regarding the involvement of AMPAR-mediated BDNF/TrkB/mTORC1 (mammalian target of rapamycin complex 1) signaling in the rapid antidepressant effects of ketamine [20,21,26] (Fig. 1).…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…2). However, Zanos et al found that both ketamine and (2R,6R)-HNK have no significant effect on mTOR phosphorylation and BDNF levels at 1 h after treatment, which is not consistent with previous studies regarding the involvement of AMPAR-mediated BDNF/TrkB/mTORC1 (mammalian target of rapamycin complex 1) signaling in the rapid antidepressant effects of ketamine [20,21,26] (Fig. 1).…”
contrasting
confidence: 54%
“…Ketamine is widely accepted to act mainly by inhibiting NMDARs in GABAergic interneurons, thus disinhibiting glutamatergic neurons, leading to the activation of downstream signaling and synaptic protein synthesis [20][21][22] (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased extrasynaptic glutamate can also bind to presynaptic neuronal metabotropic mGluR2/3 autoreceptors inhibiting glutamate release leading to chronic reductions in intrasynaptic glutamate, loss of excitatory synaptic activity, and ultimately result in synaptic loss (Duman, 2014;Duman et al, 2016;McEwen et al, 2016). Of note, mGluR2/3 antagonists have demonstrated ketamine-like antidepressant effects (Duman, 2014;McEwen et al, 2016).…”
Section: Conceptual Convergence: a Working Modelmentioning
confidence: 99%
“…46 Importantly, these 5-HT 7 receptor-mediated molecular and cellular mechanisms that have been shown to be involved in neuronal plasticity and morphology are consistent with the new insights into neurobiology of stress and mood disorders. 47 Taken together, these findings suggest that further detailed studies focused on neuronal plasticity and morphology, which may be modulated by the 5-HT 7 receptor, may be useful for understanding the mechanisms of stress adaptation.…”
Section: Discussionmentioning
confidence: 83%